Antibacterial activity of Hemidesmus indicus (L) root used by tribes of kundam, block district Jabalpur, Madhya Pradesh,(India). (Funded Work) - Shoket Ali; Shikha Bansal; Ravi Prakash Mishra (International Journal of Pharma and Bio Sciences, 2020)
The present study was aimed to examine the antibacterial activity of Hemidesmus indicus (L.). Root extract of this plant was screened against five human pathogenic bacteria in an in vitro condition. Phytochemical analysis of the root extracts indicated the presence of alkaloids, glycosides, carbohydrates, steroids, polyphenols, saponins and terpenoids. The antibacterial activity of the chloroform and aqueous extracts of root were tested by using well diffusion method and the zone of inhibition produced by extract in a dose of 50, 100 and 150 mg/ml, respectively against selected bacterial strains the overall results were compared with the standard drug ciprofloxacin (25μg/ml). Chloroform extract showed significant activity against all the tested bacteria. The biological efficiency was observed more prononced in chloroform extract in comparison to the aqueous extract against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis and Vibrio cholera with zones of growth inhibition 16.33 mm, 12.66 mm, 12.00 mm, 9.00 mm and 3.00 mm, respectively. The present study mainly focuses to explore the antibacterial properties of the root extracts of plant that are generally used as traditional medicines. The overall results showed remarkable antibacterial efficiency of the extract and can be used as potent drug against some dreadful infectious diseases caused by the test organisms.